Familial solitary chondrosarcoma resulting from germline EXT2 mutation. Issue 2 (25th October 2016) - Heddar, Abdelkader; Fermey, Pierre; Coutant, Sophie; Angot, Emilie; Sabourin, Jean‐Christophe; Michelin, Paul; Parodi, Nathalie; Charbonnier, Françoise; Vezain, Myriam; Bougeard, Gaëlle; Baert‐Desurmont, Stéphanie; Frébourg, Thierry; et al.
Abstract : Germline mutations of EXT2, encoding Exostosin Glycosyltransferase 2, are associated with multiple osteochondromas (MO), an autosomal dominant disease characterized by the development of multiple peripheral cartilaginous benign tumors with a weak risk of malignant transformation. We report here a family with a remarkable clinical presentation characterized by the development of isolated chondrosarcomas, mostly located in ribs. Comparative analysis of exomes from two third‐degree affected relatives led us to identify a single common disruptive variation, corresponding to a stop mutation (c.237G > A, p.Trp79*; (NM_000401.3); c.138G > A, p.Trp46*; (NM_207122.1)) within exon 2 of the EXT2 gene. Interestingly, no obvious sign of MO was detected in affected members by radiological examination. This report shows that germline mutations of EXT2 can result, not only in the development of multiple benign osteochondromas, but also in the development of isolated malignant cartilaginous tumors including central tumors, and that the presence of germline EXT2 mutation should be considered in patients suspected to have an inherited predisposition to chondrosarcoma, even in the absence of MO. © 2016 Wiley Periodicals, Inc.